The Effect of the PECS Method on Vocabulary Mastery of Children with Autism at SLB Negeri Purworejo - Joko Yuwono; Sugini Sugini; Nabitatus Sa'adah (Journal of Disability, 2025)
This study aims to determine the effect of the Picture Exchange Communication System (PECS) method on the vocabulary acquisition of children with autism at SLB Negeri Purworejo in the 2024/2025 academic year. The research employs a quantitative approach using a single-subject experimental method (Single Subject Research) with an A-B-A design. The subjects of the study were two ninth-grade students with autism spectrum disorder. Data were collected using a multiple-choice vocabulary test consisting of 16 items. The results showed an increase in vocabulary scores after the PECS method intervention. Data from the first baseline phase showed low and very low scores, while the intervention phase showed a stable increase. These findings indicate that the PECS method has a positive effect on the vocabulary acquisition of children with autism.